Before localization: the story of the electric rice cooker in South Korea. (3rd July 2022) - Choi, Hyungsub
ABSTRACT: The commonplace way to tell the global history of the electric rice cooker is to begin with its invention in Japan, then trace its adaptation and localization as it spread through the Asian region. This article focuses on the period before the 1990s, when rice cookers in South Korea remained inferior imitations of the Japanese models. After the introduction of the rice cooker in 1965, the South Korean engineers continued to see the Japanese rice cookers as a preferred goal that they should strive to imitate. Even the national project to overcome South Korea's reliance on Japanese rice cookers consciously aimed to copy the Japanese rice cooker as closely as possible. This episode will show that there are interesting stories to tell about imitation and replication, which required a lot more planning and technological expertise than one might expect. Thus, conscious efforts to copy foreign technologies can serve as a useful site of historical inquiry.